Assessing the role of turbulence-radiation interactions in hydrogen-enriched oxy-methane flames. (15th March 2018) - Krishnamoorthy, Gautham; Rahman, Md Ashiqur
Abstract: Statistical analysis of scalar data obtained from single-shot laser measurements in four turbulent oxy-fuel flames were carried out to develop a functional relationship for the temperature self-correlation (TSC) term for use in Turbulence Radiation Interaction (TRI) models. The developed relationship was found to be invariant with the hydrogen enrichment in the fuel, fuel jet Reynolds numbers and correlated reasonably well with the root-mean-square of temperature (Trms ). The TSC and the absorption-coefficient temperature correlation (ATC) were both modeled in terms of Trms and employed as add-on functions in time-averaged flame simulations. Including the effects of TRI enhanced the radiant fraction by 40% and reduced outlet CO concentrations by 30% across all flames. Further, there was significant flame absorption due to the high concentrations of radiatively participating gases that would deem optically thin radiation approximations in these flames to be erroneous. Highlights: Data from four hydrogen enriched oxy-methane flames was statistically analyzed. TRI closure terms formulated based on functional forms resulting from flame data. The functional relationships were invariant with fuel composition, Reynolds number. TSC and ATC approximations to the TRI enhanced emission by 30–40%. Including the effects of TRI reduced outlet CO predictions by 30%.